Morfologia de frutos e sementes e morfofunção de plântulas de Moringa (Moringa oleifera Lam.) - Ramos, Lina Maria [UNESP] (2010)
The objective of this work was to characterize external and internal morphologic aspects of the fruit, seed, and plant of Moringa oleifera Lam. The fruits were collected in the forest garden of Falculty of Agrarian and Veterinarian Sciences, São Paulo State University, Jaboticabal-SP, Brazil. It was observed that the Moringa fruits are brown simple darkness, dry of the type capsule, tends on average: 28.50 cm of length, 2.21 cm of width, 9.91 g of mass and with 12 seeds by fruit, it considerated fruits of medium and small size. The seeds are brown dark and they present three lines clear chestnut tree. The embryo is oleaginous, has a pair of cotyledons and the germination is hypogeal-cryptocotyledonary. The seed has1.037 cm of length and 1.0 cm of thickness of average and have a considerate medium and light weight (197g/1000 seeds). The germination began eight days after the planting and in the 25th day they left the primary leaves.